Fish bones in the throat. Issue 1 (March 1989) - Knight, L C; Lesser, T H
Abstract : Patients presenting with sharp pain in their throat after eating fish were studied to determine the site and frequency of impacted fish bones. In 79% no fish bone was demonstrated despite careful follow up. In those proven to have a fish bone 93% were in the oropharynx. The role of X-rays and the indications for referral for endoscopy are discussed.